The impact of foreign direct investments on the increase in the number of visitors in tourism - Case study Republic of Kosovo - Bajrami, Halil; Beha, Fejzula; Bellaqa, Bashkim; Shala, Venet (Edelweiss Applied Science and Technology, 2024)
Foreign Direct Investment (FDI) plays a significant role in the Republic of Kosovo's economy, namely in the tourist sector. The primary goal of this research is to examine the impact of FDI on the increase in the number of tourist visits (NTV), as well as the trend of NTV and government spending on recreation, culture, and religion in the Republic of Kosovo. The results demonstrate that NTV increased in Kosovo between 2008 and 2022, however this increase was not consistent. The most pronounced growth was in 2021 compared to 2020, at approximately 133%, while the most pronounced decline in NTV was in 2020 compared to 2019, at -46%. From 2008 to 2022, the FDI trend was the highest in 2022, when the value of FDI reached 778.2 million euros, while the government's expenditures in the fields of recreation, culture, and religion were the highest in 2021, at approximately 61 million euros. Empirical analysis indicates that FDI has positively impacted the expansion of NTV in Kosovo, with a β parameter of 0.41. The report suggests that state officials adopt more sustainable and effective policies that will result in higher FDI, government tourism spending, and NTV in Kosovo. A sustainable FDI policy for the tourism industry will have an impact not only on tourism, but also on other tourism-related businesses. Furthermore, a critical appraisal is required in Kosovo to improve tourism performance and regional economic development, among other things.